TEACHING DESIGN AND INDONESIAN LANGUAGE MATERIALS AT UNIVERSITIES OF THAILAND AND MANILA, PHILIPPINES, BASED ON LOCAL WISDOM IN BIPA LEARNING (DESAIN PENGAJARAN DAN MATERI BAHASA INDONESIA DI UNIVERSITAS THAILAND DAN MANILA FILIPINA, BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN BIPA) - Aninditya Sri Nugraheni; Shindy Lestari; Alma Pratiwi Husain; Eri Susanto (Jurnal Gramatika, 2022)
This research aims to present learning systems and teaching materials based on local wisdom teaching design Indonesian for foreign speakers at Thammasat University and Normal University Manila. This study uses qualitative methods and obtaining research data using participant observation (participant observation), in-depth interviews, and documentation. The results of this study show: 1)  The prospects of Indonesian in Thailand and the Philippines show that the establishment of diplomatic relations and education and become the official language of ASEAN countries, 2) BIPA learning in Indonesia  Based on the curriculum created by the Central Agency for Diplomacy, learners are targeted to master four skills: reading, writing, 3) BIPA materials in Thailand and the Philippines are tailored to the purposes of foreigners, this enabling BIPA  students to speak Indonesian in a formal and informal and familiar with Indonesian culture. 4)  Local wisdom in BIPA learning in Thailand and the Philippines introduced Indonesian culture. So, BIPA has become very important in Thailand and the Philippines because it is the language of choice of the ASEAN Economic Community.